The Communication Strategies to Avoid Conflicts When Speaking to Sasak Speakers: A Language Style Analysis - Sugianto; Tawali (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Sasak language is a language spoken by mostly whole people who live in Lombok Island, West Nusa Tenggara. As a main media of communication in Lombok, the possibility to get interact with them is wide open since Lombok had become a famous place stayed by various person from all around the world. For the sake of maintaining good relationship with people in Lombok who speak sasaknese, it is crucial to find out what kind of conflicts might happen when communicate to them. Therefore, here is the research aimed at uncovering the conflicts avoidances utilized by speakers of